Barium Aspiration in an Infant: A Case Report and Review of Management - Jackson, M.; Kapur, N.; Goyal, V.; Choo, K.; Sarikwal, A.; Masters, I. B.; Isles, Alan F. (Frontiers in Pediatrics, 2014)
We describe a case of bilateral inhalation of barium in an infant following a barium swallow for investigation of dusky spells associated with feeds. A bronchoscopy subsequently revealed the presence of a mid-tracheal tracheo-esophageal cleft. To date, little has been reported on barium aspiration in children and there is no consensus for management. We review the literature on barium aspiration, its consequences, and make recommendations for management.